New southern African species and a revalidation in the dung beetle genus Gyronotus van Lansberge, 1874 (Scarabaeidae: Scarabaeinae) with an updated key - Deschodt, Christian M.; Davis, Adrian L.v. (Zootaxa, 2019)
Three new species are described in the genus Gyronotus van Lansberge, 1874 (Scarabaeidae: Scarabaeinae), from upland grasslands of South Africa. They are Gyronotus dracomontanus Deschodt & Davis, new species, Gyronotus ovalis Deschodt & Davis, new species and Gyronotus kearneyorum Deschodt & Davis, new species. The South African coastal forest species, Gyronotus marginatus Péringuey, 1888, status revised, is removed from synonymy with Gyronotus pumilus (Boheman, 1857) and revalidated at species level. An updated key to all South African and eSwatini species is provided.